Effect of basal ganglia calcification on its glucose metabolism and dopaminergic function in idiopathic hypoparathyroidism. (27th November 2014) - Modi, Sagar; Arora, Geetanjali; Bal, Chandra Shekhar; Sreenivas, Vishnubhatla; Kailash, Suparna; Sagar, Rajesh; Goswami, Ravinder
Summary Background The functional significance of basal ganglia calcification (BGC) in idiopathic hypoparathyroidism (IH) is not clear. Objective To assess the effect of BGC on glucose metabolism and dopaminergic function in IH. Methods 18F‐FDG and 99mTc‐TRODAT‐1 nuclear imaging were performed in 35 IH patients with (n = 26) and without (n = 9) BGC. Controls were subjects without hypoparathyroidism or BGC (nine for 18F‐FDG and 12 for 99mTc‐TRODAT‐1). Relationship of the glucose metabolism and dopaminergic function was assessed with the neuropsychological and biochemical abnormalities. Results 18F‐FDG uptake in IH patients with calcification at caudate and striatum was less than that of IH patients without calcification (1·06 ± 0·13 vs 1·24 ± 0·09, P = <0·0001 and 1·06 ± 0·09 vs 1·14 ± 0·08, P = 0·03, respectively). 18F‐FDG uptake did not correlate with neuropsychological dysfunctions. 18F‐FDG uptake in IH without BGC was significantly lower than that of controls. The mean 99mTc‐TRODAT‐1 uptake at basal ganglia was comparable between IH with and without BGC and between IH without BGC and controls. Serum calcium–phosphorus ratio maintained by the patients correlated with 18F‐FDG uptake at striatum (r = 0·57, P = 0·001). For every 0·1 unit reduction in calcium–phosphorus ratio, 18F‐FDG uptake decreased by 2·5 ± 0·68% (P = 0·001). Conclusion BGC was associated with modest reduction (15%) in 18F‐FDG uptake at basal ganglia in IH but did not affect dopaminergic function. 18F‐FDG uptake did not correlate with neuropsychological dysfunctions. Interestingly, chronic hypocalcaemia–hyperphosphataemia also contributed to reduction in 18F‐FDG uptake which was independent of BGC.